Alleviating lead-induced phytotoxicity and enhancing the phytoremediation of castor bean (Ricinus communis L.) by glutathione application: new insights into the mechanisms regulating antioxidants, gas exchange and lead uptake. Issue 9 (29th July 2022) - Bamagoos, Atif A.; Mallhi, Zahid Imran; El-Esawi, Mohamed A.; Rizwan, Muhammad; Ahmad, Awais; Hussain, Afzal; Alharby, Hesham F.; Alharbi, Basmah M.; Ali, Shafaqat
Abstract: Heavy metals pollution represents a serious issue for cultivable lands and ultimately threatens the worldwide food security. Lead (Pb) is a menacing metal which induces toxicity in plants and humans. Lead toxicity reduces the photosynthesis in plants, resulting in the reduction of plant growth and biomass. The excessive concentration of Pb in soil accumulates in plants body and enters into food chain, resulting in health hazards in humans. The phytoremediation is eco-friendly and cost-efficient technique to clean up the polluted soils. However, to the best of our Knowledge, there are very few reports addressing the enhancement of the phytoremediation potential of castor bean plants. Therefore, the present study aimed to investigate the potential role of glutathione (GSH), as a promising plant growth regulator, in enhancing the lead stress tolerance and phytoremediation potential of castor bean plants grown under lead stress conditions. The results indicated that Pb stress reduced the growth, biomass, chlorophyll pigments and gas exchange attributes of castor bean plants, causing oxidative damage in plants. Pb stress induced the oxidative stress markers and activities of antioxidant enzymes. On the other hand, the application of GSH reduced oxidative stress markers, but enhanced the growth, biomass, photosynthetic pigments, gas exchange attributes, Pb accumulation and antioxidant enzymes activities of lead-stressed castor bean plants. Both Pb uptake and Pb accumulation were increased by increasing concentrations of Pb in a dose-additive manner. However, at high dose of exogenous GSH (25 mg L −1 ) further enhancements were recorded in the Pb uptake in shoot by 48% and in root by 46%; Pb accumulation was further enhanced in shoot by 98% and in root by 101% in comparison with the respective control where no GSH was applied. Taken together, the findings revealed the promising role of GSH in enhancing the lead stress tolerance and phytoremediation potential of castor bean ( Ricinus communis ) plants cultivated in Pb-polluted soils through regulating leaf gas exchange, antioxidants machinery, and metal uptake. Novelty statement: The excessive concentration of Lead (Pb) in soil accumulates in plants body and enters into food chain, resulting in health hazards in humans. Phytoremediation is eco-friendly and cost-efficient technique to clean up the polluted soils. However, to the best of our knowledge, there are very few reports addressing the enhancement of the phytoremediation potential of castor bean plants. Therefore, the novelty of this research is that this research studied the potential role of glutathione (GSH), as a promising plant growth regulator, in enhancing the lead stress tolerance and phytoremediation potential of castor bean plants grown under lead stress conditions. The results indicated that Pb stress reduced the growth, biomass, chlorophyll pigments and gas exchange attributes of castor bean plants, causing oxidative damage in plants. Pb stress induced the oxidative stress markers and activities of antioxidant enzymes. On the other hand, the application of GSH reduced oxidative stress markers, but enhanced the growth, biomass, photosynthetic pigments, gas exchange attributes, Pb accumulation and antioxidant enzymes activities of lead-stressed castor bean plants. Taken together, the findings revealed the promising role of GSH in enhancing the lead stress tolerance and phytoremediation potential of castor bean plants cultivated in lead-polluted soils.